Framing Science: How Opioid Research Is Presented in Online News Media - Matthias, Lisa; Fleerackers, Alice; Alperin, Juan Pablo (Frontiers in Communication, 2020)
Popular news media play an instrumental role in shaping public perception of issues like the opioid crisis. Using a detailed coding instrument, we analyzed how opioid-related scholarly publications were covered in 149 news stories published by nine major US and Canadian online news outlets at the height of the crisis. We find that a small proportion of available studies receive coverage, mostly within issue-focused rather than science communication news stories. While most studies are framed as established “facts”, stories rarely provide sufficient information for news consumers to critically evaluate the validity of the research. Potential implications for science communication and public perception of the opioid crisis are discussed.